Reliability certification of software components - Wohlin, C.; Regnell, B. (Proceedings. Fifth International Conference on Software Reuse (Cat. No.98TB100203), 1998)
Reuse is pin-pointed as a key factor to improve productivity and reliability of software systems. Verification and validation of software components and the resulting system is important for reuse to be beneficial on a broad industrial basis. The paper suggests a modelling approach which is suitable for reliability certification of modular systems. It discusses a general reliability certification procedure and provides guidelines and opportunities for how to certify software components and also presents some alternatives for certification of modular systems. We conclude that to create reliable systems, we must start certifying the individual constituents of the systems.